The PID Principles of Care: Where Are We Now? A Global Status Report Based on the PID Life Index - Nordin, Julia; Solís, Leire; Prévot, Johan; Mahlaoui, Nizar; Chapel, Helen; Sánchez-Ramón, Silvia; Ali, Adli; Seymour, John W.; Pergent, Martine (Frontiers in Immunology, 2021)
A global gold standard framework for primary immunodeficiency (PID) care, structured around six principles, was published in 2014. To measure the implementation status of these principles IPOPI developed the PID Life Index in 2020, an interactive tool aggregating national PID data. This development was combined with a revision of the principles to consider advances in the field of health and science as well as political developments since 2014. The revision resulted in the following six principles: PID diagnosis, treatments, universal health coverage, specialised centres, national patient organisations and registries for PIDs. A questionnaire corresponding to these principles was sent out to IPOPI’s national member organisations and to countries in which IPOPI had medical contacts, and data was gathered from 60 countries. The data demonstrates that, regardless of global scientific progress on PIDs with a growing number of diagnostic tools and better treatment options becoming available, the accessibility and affordability of these remains uneven throughout the world. It is not only visible between regions, but also between countries within the same region. One of the most urgent needs is medical education. In countries without immunologists, patients with PID suffer the risk of remaining undiagnosed or misdiagnosed, resulting in health implications or even death. Many countries also lack the infrastructure needed to carry out more advanced diagnostic tests and perform treatments such as hematopoietic stem cell transplantation or gene therapy. The incapacity to secure appropriate diagnosis and treatments affects the PID environment negatively in these countries. Availability and affordability also remain key issues, as diagnosis and treatments require coverage/reimbursement to ensure that patients with PID can access them in practice, not only in theory. This is still not the case in many countries of the world according to the PID Life Index. Although some countries do perform better than others, to date no country has fully implemented the PID principles of care, confirming the long way ahead to ensure an optimal environment for patients with PID in every country.